Supersaturation of body fluids, plasma and urine, with respect to biological hydroxyapatite - Söhnel, Otakar; Grases, Felix (Urological research, 2011)
Supersaturation of body fluids, specifically of plasma and urine, with respect to biological hydroxyapatite was evaluated taking into account calcium complexation, fraction of total phosphorus present as hydrogen phosphate ions, solubility of carbonated hydroxyapatite and the size dependency of equilibrium solubility. Plasma is always supersaturated with respect to apatitic solid phase and thus calcific deposits are formed unless a sufficient quantity of potent inhibitors is present. When urinary pH is lower than 6.3 for normal urine hydroxyapatite cannot appear in renal stones, at higher pH apatitic renal stones can be formed. Predictions based on supersaturation calculated for different conditions correspond well with clinical observations.
Keywords: tělesné tekutiny; fosfáty; vápník; lidé; Durapatite; Hydrogen-Ion Concentration; Body Fluids; Calcium; hydroxyapatit; biologické modely; koncentrace vodíkových iontů; Phosphates; Models, Biological; Humans